A Study Of Adjusting Distribution Transformer Capacity To Consumer Loads At PT PLN (Persero) ULP Medan Johor - Yunus Mendrofa; Davet Widy Affandi; Maghfirah Sekar Tanjung; Renaldy Darma Putra Sitorus; Wiwit Mardika Siallagan; Solly Aryza (INFOKUM, 2025)
The distribution transformer is a very vital component for medium voltage distribution systems. However, it is not uncommon for distribution transformers to experience interference. One of them is transformer overload. The cause of the overload is the load attached to the transformer which becomes hot and results in an increase in the winding temperature in the transformer coil. The increase in winding temperature can cause damage to the winding insulation on the transformer coil which is at risk of damage to the transformer and can result in the interruption of electricity distribution to consumers. According to references, ideally a transformer is loaded at 80% of the maximum capacity of the transformer. But the reality in the field is that there are still many distribution transformers that are loaded beyond their maximum capacity. One effort that can be done to deal with this is to increase the power capacity (uprating). After the distribution transformer uprating activity, it can be seen that the percentage of load served by the distribution transformer which was previously overloaded can be reduced.